Elaboration of a pasteurized beverage from a quinoa (Chenopodium quinoa Willd.) protein extract - Guallasamín Dávila, Andrea Estefanía; Ávila Vélez, Jenny Marcela; Sotomayor Grijalva, María Cristina (Enfoque UTE, 2018)
The research consisted on evaluating parameters to obtain a quinoa beverage. Quinoa soluble protein (SP) extraction and two process conditions (addition of stabilizer and pasteurization temperature) were considered as parameters. The concentration of SP in the protein extract was studied through the factors: flour:NaOH solution ratio (1:2.50, 1:3.25 and 1:4.00), conditioning temperature (20 and 45 ºC), and pH (7.50 and 8.00), for 30 min at laboratory scale. The protein extract with the highest SP concentration was replicated at pilot scale, and white sugar, vanilla flavor and stabilizer (0.00 and 0.25 %) were added to formulate beverage. Then, the pasteurization temperature (120 and 135 ºC) was evaluated. The independent variables: soluble protein variation (SPVb), suspension percentage and microbial population reduction (MPR) were measured at day 0. The protein extract that was obtained with a flour-NaOH solution ratio of 1:3.25, 20 ºC and pH 7.5 reached 77.10 ± 1.76 %. The beverage had a VPSb -2.36 ± 0.25 %, a suspension percentage of 98.33 ± 1.53 % and 2.36 % of protein at 120 ºC with stabilizer 0.25 %.